Diversity and Copepods’composition off Moroccan Atlantic Coast (Northwest Africa): A Review - Laila El Arraj; Ouadiaa Tazi; Laila Somoue; Karim Hilmi; Mansour Serghini; Omar Ettahiri (European Scientific Journal, ESJ, 2017)
This overview sums up the results of main investigations and knowledge about zooplankton off Moroccan Atlantic coast. Copepods diversity, spatial distribution, seasonal variability and hydrology off Moroccan Atlantic coast are given. A compilation of taxonomic list of copepods’ species found therein was established from published studies, they accounted for 210. Diversity and richness varied strongly between seasons, an onshore offshore gradient was observed as well. Species composition differed from northern to southern Moroccan Atlantic coast although most dominant species off Morocco’s coasts were Calanus helgolandicus, Paracalanus parvus, Acartia clausi and Corycaeus typicus. In addition, the largest number of species was found in upwelling regions. A synthesis study was established in order to spatial distribution of copepods along Moroccan Atlantic coast. The Factorial Correspondence Analysis of copepod species characterizing the most important sectors has shown different patterns of copepods distribution across Moroccan Atlantic coast; three main areas were clearly segregated according to their taxonomic composition (Northern, Central and Southern Atlantic).